The Specifics of Stimulating Representatives of the Insurance Business ("Journal "U". Economy. Management. Finance.", 2022)
The importance of incentive problems is not disputed by either science or practice, since not only the increase in the social and creative activity of a particular employee, but also the final results of the activity depend on the clear development of an effective incentive system. In the context of insurance activities, incentives include many different features that have a direct effect on the performance of an insurance company representative.
Keywords: management; motivation; remuneration; incentives; insurance; insurance business; personnel management